Precious corals (Octocorallia: Coralliidae) from the northern West Pacific region with descriptions of two New Species - Tu, Tzu-Hsuan; Dai, Chang-Feng; Jeng, Ming-Shiou (Zootaxa, 2012)
Members of the family Coralliidae, known as precious corals, are ecologically and economically important deep-sea or-ganisms. However, these organisms are currently threatened by commercial harvesting. In order to create and implementeffective conservative strategies, taxonomic knowledge of conservative targets is necessary, but unfortunately the taxon-omy of precious corals in this family is still ambiguous. This study provides a review of 15 Coralliidae species from thenorthern West Pacific region and a key to species identification. In addition, descriptions of two new species, Coralliumcarusrubrum n. sp. and C. taiwanicum n. sp., as well as a redescription of C. sulcatum Kishinouye, 1903 are included.Corallium carusrubrum n. sp. is distributed on seamounts off northeastern Taiwan. The autozooids of C. carusrubrum n.sp. are retractile and each can be fully withdrawn into the cortex thereby causing a mound on the surface which is shortand cylindrical rather than typically hemispherical; additionally, there are no long spindles in their tentacles. Coralliumtaiwanicum n. sp. is distributed in an area off southwestern Taiwan. It has special unique 8-radiates with an oval shapeand large projections. Corallium sulcatum is distributed from an area off southwestern Taiwan to western Japan. It hasbeen harvested and traded for decades, but there were no illustrations in its original description, hence a redescription of this species is provided.